2 - L’Université de Kinshasa : « colline du savoir », colline des transactions - Bernard Mumpasi Lututala (Journal of Higher Education in Africa, 2012)
The decades-long crisis in the Congolese tertiary education is well known by those interested in higher education in Africa. It is often explained by the deplorable conditions and the meager resources with which the university operates. So one wonders why the Congolese state does not try to improve the situation. Here is a hypothesis: The Congolese University pays for its resistance to the political power in place. Therefore, its “reconciliation” with the State is a condition of its rehabili- tation. But who must be reconciled with whom? The Congolese university has continued, despite everything, to operate somehow and to fulfill the missions of a recognized university, so it is for the Congolese State to end its embargo. Any other solution will only be palliative and will not provide lasting results.